2012
DOI: 10.1172/jci62237
|View full text |Cite
|
Sign up to set email alerts
|

Synergy of understanding dermatologic disease and epidermal biology

Abstract: Dermatologic disease, although seldom life threatening, can be extremely disfiguring and interfere with the quality of life. In addition, as opposed to other organs, just the aging of skin and its adnexal structure the hair follicle can result in cosmetic concerns that affect most of us. The articles in this dermatology Review Series demonstrate recent progress in understanding the cell biology and molecular pathophysiology of the epidermis and hair follicles, which harbor keratinocyte and melanocyte stem cell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 25 publications
0
6
0
Order By: Relevance
“…Thus, it is plausible that modulating the MC1R pathway might contribute to improvement to pigmentary disorders such as vitiligo, melasma, or postinflammatory hyper/hypopigmentation [94] . Furthermore, other clinical and cosmetic implications of MelSCs have been postulated in a review by Stanley [95] . Considering stem cell anatomy and biology, permanent hair removal by electrolysis or laser treatment should be focused on eliminating the hair bulge, even though there is some difficulty in targeting selectively the bulge areas.…”
Section: Melanocyte Stem Cells In Human Skin Disordersmentioning
confidence: 99%
“…Thus, it is plausible that modulating the MC1R pathway might contribute to improvement to pigmentary disorders such as vitiligo, melasma, or postinflammatory hyper/hypopigmentation [94] . Furthermore, other clinical and cosmetic implications of MelSCs have been postulated in a review by Stanley [95] . Considering stem cell anatomy and biology, permanent hair removal by electrolysis or laser treatment should be focused on eliminating the hair bulge, even though there is some difficulty in targeting selectively the bulge areas.…”
Section: Melanocyte Stem Cells In Human Skin Disordersmentioning
confidence: 99%
“…Histological changes in chronologically aged skin are characterized by decreased recovery capacity, altered permeability of the stratum corneum, epidermal atrophy particu-2 of 17 larly affecting the stratum spinosum, and decreased amounts of fibroblasts and collagen in the dermis (Figure 1). The stratum corneum consists of corneocytes, which are anulceated keratinocytes retaining keratin filaments within a filaggrin matrix and surrounded by a cornified lipid envelope; they organize into a brick-and-mortar formation within the ECM, forming lipid-rich membranes [6]. A recent biochemical study using cadaveric donors found that the stratum corneum, especially the keratin fibers in chronologically aged skin, stiffens with aging.…”
Section: Histology Of Chronological Aging and Photoagingmentioning
confidence: 99%
“…Stratum corneum [6][7][8] Epidermal atrophy [9,10] Langerhans cells [11] Dermis Fibroblast senescence [13,14,44] Collagen structure [15][16][17][18]43,44] Elastic fibers [22,23] Photoaging Epidermal thickness [25,26] Cell atypism [27] Solar elastosis [32,34,36,38,40]…”
Section: Epidermismentioning
confidence: 99%
“…The stratum corneum, the outermost layer of the epidermis, consists of corneocytes arranged in compact sheets that are embedded in an extracellular matrix derived from lamellar granules forming lipid-rich membranes. 10,11 This cornified layer acts as the outermost interface between the atmosphere and the underlying epidermal and dermal tissues. The thickness of the stratum corneum can be dynamic throughout life, and it can become thickened in response to various insults or inflammatory conditions.…”
Section: The Structural Realities Of Chronologic Aging Versus Photoagingmentioning
confidence: 99%